Subliminal Paradigmatic on Designing Character in Games - Sulaiman Hakim Lubis; Tubagus Zufri (Journal of Games, Game Art, and Gamification, 2020)
Not only rely on aesthetics alone, but character design also requires things that underlie decision making in the design process. The consideration may refer to the type of story, style and appearance that also refers to the form, which is part of the elements of design, but other than those designers must also be paid attention to other things that related with the problem that occurs when the game is played. Games will be played by players who in fact have experiences that will later be brought into the game and instead bring experience from within the game to the real world. This unconscious condition can also be used as a design consideration.